LEGAL AWARENESS DEVELOPMENT MODEL THROUGH A RELIGIOUS APPROACH: (Case Study at the Sumenep Class II-B State Detention Center) - ., Imalah (JURNAL SETIA PANCASILA, 2023)
The high recidivism in Indonesia based on data from the ministry of law and human rights in 2020 amounted to 18.12% or around 24 thousand people clearly demands strategic policy steps in order to reduce the level of recidivism in Indonesia, the Sumenep Class IIB State Detention Center as a technical implementing unit under the auspices of the Directorate General Corrections Department of Law and Human Rights of the Republic of Indonesia where the main task and function is to provide guidance in order to ensure positive behavior changes. The purpose of this study was to find out how the pattern of fostering legal awareness through a religious approach at the Sumenep Class II-B State Detention Center and how the legal awareness of the inmates after coaching is carried out. Through a qualitative approach, data is obtained through observation, interviews, and documentation. The findings of this study indicate that the pattern of fostering inmates at the Sumenep Class II-B State Detention Center is carried out using personality and independence development methods by using special methods such as religious approaches by increasing the legal awareness of inmates,habituating behavior such as disciplinary habits the five daily prayers and congregational prayers, routine recitation, reading and writing of the Qur'an, and istighasah are relatively high and have a very significantimpact on increasing the legal awareness of inmates in the Sumenep Class II-B State Detention Center.